Insilico analysis of three different tag polypeptides with dual roles in scFv antibodies. (7th August 2016) - Mohammadi, Mozafar; Nejatollahi, Foroogh; Sakhteman, Amirhossein; Zarei, Neda
Abstract: Single chain fragment variable (scFv) antibodies are composed of variable heavy ( VH ) and variable light ( VL ) domains that are joined by a polypeptide linker. Typically, [(Gly4 Ser) n] sequence is used as a linker to retain the integrity of the antigen-binding domain. Due to its low immunogenicity, this sequence cannot be used as a tag for scFv detection and purification. Several evidences have shown that the addition of an N or C-terminal tag for scFv detection and purification will result in the decreased expression and binding capacity of this antibody fragment. In this study, we substituted the traditional linker (GGGGS) with His-tag, C-myc or E-tag sequences through molecular modeling. Stability and integrity of all models were assessed by molecular dynamic (MD) simulation. Based on MD simulation analysis, the model containing E-tag sequence as a linker indicated more stability compared to other molecules. The results suggest that E-tag not only can be substituted for the traditional linker, also eliminates the necessity of using additional tag for scFv detection and purification. Highlights: Due to low immunogenicity of traditional linker (GGGGS) of scFv antibodies, it cannot be used as a tag for scFv detection and purification. We substituted the traditional linker with His-tag, C-myc or E-tag sequences through molecular modeling. Stability and integrity of all models were assessed by molecular dynamic (MD) simulation.